Justification of using a modified RME protocol with myofunctional appliances for dental crowding treatment of mixed dentition period patients with different facial skeleton growth patterns. - Krymovskyy, Kyryl; Kaniura, Oleksandr; Kostiuk, Tetiana (The Ukrainian Scientific Medical Youth Journal, 1970)
the pathology of dental crowding in  mixed dentition period is one of the most common in orthodontic practice. Its prevalence, according to various worldwide scientific sources, reaches 77% and occurs at all stages of the formation of the dentognathic system, sometimes complicating the existing malocclusion. The purpose of our study is to create a rational treatment protocol for patients with dental crowding  according to the facial skeleton growth pattern, as well as to conduct a comparative analysis of the effectiveness of dental crowding treatment according to standard and suggested protocol. A three-year study at NMU O.O. Bogomolets Medical Center  of patients with dental crowding in mixed dentition period(164 people).A total of 328 CBCT slices before and after treatment of patients with crowded teeth were submitted to the overall analysis. The results and conclusions of treatment efficiency analysis were carried out using the proposed treatment protocol with different facial skeleton growth patterns indicate an increase in the quality of treatment of this pathology and a reduction in  treatment terms to achieve the result. The results obtained after 16 months in patients with a horizontal type of growth indicate that the effectiveness of the treatment of CG II patients reached 68.1±1.3%;after 17 months, in patients with a vertical and neutral growth patterns, the effectiveness of treatment of CG III reached 76.7±1.6%, CG I – up to 62.3±0.7%. The algorithm proposed by us allows  to shorten the treatment period by 3-4 months.